مدى استخدام مراجع الحسابات الخارجي لإجراءات المراجعة التحليلية في ظل معيار المراجعة الدولي (520) / دراسة عملية اختبارية / - الأمين, ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر المراجعة التحليلية اتجاها من الاتجاهات الحديثة في مهنة المراجعة, فهي تعتمد على إجراءات متعددة لعناصر القوائم المالية للمنشأة محل المراجعة, وصولاً لقناعات ودلالات حولها. فقد ازداد الاهتمام بالمراجعة التحليلية بسبب زيادة المنافسة على خدمة المراجعة وأتعابها, وانتشار نظم المعلومات المحاسبية الالكترونية, ولقدرتها على تخفيض تكلفة خدمة المراجعة وزيادة فعاليتهاهذا من جهة, ومن جهة ثانية أصبحت دليل إثبات يمكن الاعتماد عليه في تكوين رأي المراجع بالبيانات المالية المقدمة له. وهذا البحث يسلط الضوء على مدى تطبيق هذا الأسلوب والوقوف على الصعوبات التي تواجهه, وتحديد العوامل المؤثرة على استخدامه بما ينسجم مع معيار المراجعة الدولي رقم (520), وذلك من خلال تحليل نتائج عينة إحصائية عشوائية من المراجعين المزاولين للمهنة بالاعتماد على استبيان يتضمن مجموعة من الأسئلة تلبي فروض البحث المصاغة. Analytic auditing is one of the modern directions at the profession of auditing. It depends on different procedures concerning the elements of the financial lists at the foundation we are auditing, getting certain facts and hints about it. The concern with the analytic auditing is increasing because of the increase in competition on the auditing service and its costs, and the spread of the electronic accounting informatics and its ability to decrease the cost of the auditing service, increasing its efficiency and becoming dependable evidence on the side of the auditors in making ideas about the financial data introduced to them. This research brings into light the range of application of this attitude and illustrates the obstacles facing it, besides determining the elements that effect its use in accordance with the international auditing range 520, all of these through analyzing the results taken from random statistic samples of auditing at this profession depending on a questionnaire that contains a group of questions that answers the needs of the research.